Further constraints on a Neoproterozoic active continental margin from sandstones of the Hengdan Group in the Bikou Terrane, northwestern margin of the Yangtze Block, South China. (November 2020) - Gao, Feng; Pei, Xianzhi; Li, Ruibao; Li, Zuochen; Pei, Lei; Chen, Youxin; Wang, Meng; Zhao, Shaowei; Liu, Chengjun; Li, Xiaobing
Graphical abstract: Highlights: Neoproterozoic igneous rocks in the Micangshan-Hannan massifs were the sources for sandstones of the Hengdan Group. Hengdan Group was most likely deposited in a forearc basin during ca. 733–717 Ma. Northwestern margin of the Yangtze Block was likely an active continental margin during ca. 835–720 Ma. Top-down process could be the dominant rifting mechanism in the supercontinental margin(s). Abstract: The Neoproterozoic Hengdan Group in the northwestern margin of the Yangtze Block preserves archives for the debated early to middle Neoproterozoic (ca. 835–720 Ma) tectonic evolution of the margin of the Yangtze Block, and could potentially shed lights on the breakup mechanism of the Rodinia supercontinent. However, its depositional age, provenance and tectonic setting remain controversial. We address these issues through studies of petrography, geochemistry and detrital zircon U-Pb ages on the Hengdan Group sandstones. The Hengdan Group sandstones have low compositional and textural maturity and experienced low degree of chemical weathering and sediment recycling. They were mainly sourced from proximal acidic to intermediate arc-related igneous rocks, and their modal compositions, trace elemental contents (i.e., La, Ce, Th, and ΣREE) and ratios (i.e., LaN /YbN and Eu/Eu*) are comparable to those deposited in an active continental margin. Detrital zircons from the Hengdan Group sandstones yield similar unimodal age distributions at 950–740 Ma, with the youngest age clusters at ca. 730 Ma. Combining with previous work, the Hengdan Group was most likely deposited during ca. 733–717 Ma in a forearc basin and its primary provenance was probably from the nearby arc-related acidic to intermediate igneous rocks. In addition, the northwestern margin of the Yangtze Block was most likely in an active continental margin setting between ca. 835 and 720 Ma, and hence the slab retreating during a long-term oceanic subduction is favored as the dominant breakup driving force in the supercontinental margin(s).